Using Word Wall Website to Enhance Students' Vocabulary: A Case Study of Daily Activities - Syahrida, Syahrida; Sunra, La; Surianti, Mahyar Fitri (Universitas Negeri Makassar, 2024)
Abstract. The objective of this study is to investigate how the utilization of Word Wall website as an instructional tool impacts the enhancement of students' common vocabulary usage in the context of Daily Activities. The research employed a Classroom Action Research approach, utilizing data from pre-tests, cycle reflections, and post-tests to monitor students' progress throughout the learning process. The study involved 25 students from class VII C at UPT SMPN Benteng Utara No 04 Kepulauan Selayar as research participants. Data gathered from the pre-test, cycle reflections, and post-test were subjected to analysis through the calculation of average scores and their categorization into different groups. The results of this investigation, which centered on the implementation of Word Wall website for teaching Daily Activities, indicated a significant improvement in students' performance. Initially, 64% of the students were classified as having low proficiency (Very Low and Low) in the subject. However, by the conclusion of cycle 2, as indicated by the post-test data, none of the students remained in the low category; instead, they had all progressed to the 'High and Very High' category. Keywords: Word Wall Website, common vocabulary, daily activities